EXPRESSION OF HEAT SHOCK PROTEINS (HSP70 & HSC70) AND RESPONSIVENESS OF MELATONIN RECEPTORS (MT1 & MT2) IN SPLEEN OF SWISS ALBINO MICE SUBJECTED TO HYPERTHERMIC STRESS CONDITION - SAMIK ACHARJEE; SHIV SHANKAR SINGH (International Journal of Pharma and Bio Sciences, 2014)
The most universal phenomenon in the thermal stress physiology is the expression of heat shock proteins (Hsps) following application of heat stress stimuli. Heat shock proteins are involved in the activation process of the cellular defence mechanism. Melatonin is well known as an anti-stress molecule and protects cells and tissues as an antioxidant. Melatonin also exerts hypothermic effects. Present study is mainly focused on the evaluation of expression pattern of melatonin receptors (Mt1 & Mt2) and heat shock proteins (Hsp70 & Hsc70) in an immunomodulatory organ, spleen of mice at different temperatures. Heat shock treatments against different temperature gradient (410C and 430C for 45 minutes) brought about a significant increase in the Hsp70/Hsc70 proteins and melatonin receptor Mt2 expression and decrease in Mt1 receptor expression in the spleen of experimental mice groups. Interestingly, Mt2 receptor responded in all experimental conditions corresponding to changes in Hsp70/Hsc70 protein expressions. Therefore, our present study suggests that Mt2 receptor and heat shock proteins (Hsp70 & Hsc70) are mainly responsive and probably involved in the thermoregulation process of thermally stressed mice.